Prevalence of Antimicrobial Use in a Network of Canadian Hospitals in 2002 and 2009. Issue 1 (2015) - Taylor, Geoffrey; Gravel, Denise; Saxinger, Lynora; Bush, Kathryn; Simmonds, Kimberley; Matlow, Anne; Embree, Joanne; Le Saux, Nicole; Johnston, Lynn; Suh, Kathryn N; Embil, John; Henderson, Elizabeth; et al.
Abstract : BACKGROUND: Increasing antimicrobial resistance has been identified as an important global health threat. Antimicrobial use is a major driver of resistance, especially in the hospital sector. Understanding the extent and type of antimicrobial use in Canadian hospitals will aid in developing national antimicrobial stewardship priorities. METHODS: In 2002 and 2009, as part of one-day prevalence surveys to quantify hospital-acquired infections in Canadian Nosocomial Infection Surveillance Program hospitals, data were collected on the use of systemic antimicrobial agents in all patients in participating hospitals. Specific agents in use (other than antiviral and antiparasitic agents) on the survey day and patient demographic information were collected. RESULTS: In 2002, 2460 of 6747 patients (36.5%) in 28 hospitals were receiving antimicrobial therapy. In 2009, 3989 of 9953 (40.1%) patients in 44 hospitals were receiving antimicrobial therapy (P<0.001). Significantly increased use was observed in central Canada (37.4% to 40.8%) and western Canada (36.9% to 41.1%) but not in eastern Canada (32.9% to 34.1%). In 2009, antimicrobial use was most common on solid organ transplant units (71.0% of patients), intensive care units (68.3%) and hematology/oncology units (65.9%). Compared with 2002, there was a significant decrease in use of first-and second-generation cephalosporins, and significant increases in use of carbapenems, antifungal agents and vancomycin in 2009. Piperacillin-tazobactam, as a proportion of all penicillins, increased from 20% in 2002 to 42.8% in 2009 (P<0.001). There was a significant increase in simultaneous use of >1 agent, from 12.0% of patients in 2002 to 37.7% in 2009. CONCLUSION: From 2002 to 2009, the prevalence of antimicrobial agent use in Canadian Nosocomial Infection Surveillance Program hospitals significantly increased; additionally, increased use of broad-spectrum agents and a marked increase in simultaneous use of multiple agents were observed.